Article RETRACTED due to manipulation by the authors The role of sport psychology in improving the performance of badminton athletes: a systematic review - Bafirman Bafirman; Rezha Arzhan Hidayat; Muhamad Ichsan Sabillah; Dally Rahman; Fiky Zarya; Yovhandra Ockta; Rifqi Festiawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. Sports psychology plays a vital role in improving the performance of badminton athletes. Psychological factors such as motivation, competitive anxiety, concentration, and mental resilience have been identified as critical influences on athlete performance. This study aims to systematically review the existing literature to identify and analyze the role of sports psychology in improving badminton athlete performance. The researcher searched for journal articles, books, and research reports relevant to sports psychology and badminton from various electronic databases through a systematic literature review approach. Specific inclusion criteria were applied to select studies that explicitly addressed the effect of psychological interventions on the performance of badminton athletes. Data analysis was conducted qualitatively to synthesize findings from the literature chosen. The literature review revealed that psychological techniques, including goal setting, relaxation techniques, visualization, and mental toughness coaching, positively impact the performance of badminton athletes. Findings suggest that psychological training integrated into athlete training programs can increase motivation, reduce competitive anxiety, strengthen concentration, and build mental resilience, all critical factors in athletic achievement. Sports psychology is a critical element in the training of badminton athletes, with significant potential to improve athlete performance. Psychological interventions tailored to the individual needs of athletes hold promise in optimizing athletic potential and achieving competitive success. Future research is needed to understand better how to best integrate these psychological techniques into the training of badminton athletes and to design more effective training programs that take full advantage of the role of sports psychology.